Carboxylates and alcohols production in an autotrophic hydrogen‐based membrane biofilm reactor. Issue 6 (30th March 2021) - Calvo, Diana C.; Ontiveros‐Valencia, Aura; Krajmalnik‐Brown, Rosa; Torres, Cesar I.; Rittmann, Bruce E.
Abstract: Microbiological conversion of CO2 into biofuels and/or organic industrial feedstock is an excellent carbon‐cycling strategy. Here, autotrophic anaerobic bacteria in the membrane biofilm reactor (MBfR) transferred electrons from hydrogen gas (H2 ) to inorganic carbon (IC) and produced organic acids and alcohols. We systematically varied the H2 ‐delivery, the IC concentration, and the hydraulic retention time in the MBfR. The relative availability of H2 versus IC was the determining factor for enabling microbial chain elongation (MCE). When the H2 :IC mole ratio was high (>2.0 mol H2 /mol C), MCE was an important process, generating medium‐chain carboxylates up to octanoate (C8, 9.1 ± 1.3 mM C and 28.1 ± 4.1 mmol C m −2 d −1 ). Conversely, products with two carbons were the only ones present when the H2 :IC ratio was low (<2.0 mol H2 /mol C), so that H2 was the limiting factor. The biofilm microbial community was enriched in phylotypes most similar to the well‐known acetogen Acetobacterium for all conditions tested, but phylotypes closely related with families capable of MCE (e.g., Bacteroidales, Rhodocyclaceae, Alcaligenaceae, Thermoanaerobacteriales, and Erysipelotrichaceae) became important when the H2 :IC ratio was high. Thus, proper management of IC availability and H2 supply allowed control over community structure and function, reflected by the chain length of the carboxylates and alcohols produced in the MBfR. Abstract : Membrane delivers electron‐donor H2 to bacteria growing as a biofilm in the exterior, and they produce acetate, propionate, butyrate, caproate, octanoate, ethanol, and butanol using bicarbonate as the carbon source.